2019
DOI: 10.3390/su12010121
|View full text |Cite
|
Sign up to set email alerts
|

What Park Visitors Survey Tells Us: Comparing Three Elevated Parks—The High Line, 606, and High Bridge

Abstract: Many cities have replaced abandoned transportation infrastructure with an elevated park to gain increased economic benefits by developing old fabric. By following this trend, most studies to this point have only focused on the economic rewards from the replacement rather than its uses in the real world. This study aims to understand how park visitors use elevated parks through a park visitors' survey. The authors selected three representative elevated parks-the High Line in New York City, the 606 in Chicago, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Our user composition results generally align with previous studies (Sim et al, 2020; Veitch et al, 2015). We saw more females than males in both sites (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our user composition results generally align with previous studies (Sim et al, 2020; Veitch et al, 2015). We saw more females than males in both sites (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…So more handbags seen in the High Line may indicate a lower level of usage of physical exercises for females. This resonates with Sim et al (2020) who found that the High Line could not accommodate high-intensity physical activities. Elevated urban greenways have limitations to support physical activities since facilities such as bike lanes, skate ramps, drainages, and fences are usually more expensive to construct.…”
Section: Indications On User Experiences Activities and Interactionssupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, the greenway footpath appears to have lower connectivity than the sidewalk. According to Sim et al [ 68 ], connectivity is an important characteristic of an elevated park because it allows pedestrians to access the surrounding areas [ 69 ]. In this respect, not only is the greenway footpath of Seoullo difficult to access from the sidewalk, it is also not connected to the surrounding areas.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of visitors to the park jumped from 4 Additionally, the High Line Project represents a successful example of green roofs that engage people with nature. The total number of visitors to the park jumped from 4 million people in 2011 to 7 million in 2018 [54]. This has led the project to become one of the most visited places in New York City and on the list of top New York City landmarks [ibid].…”
Section: Lessons On Biophiliamentioning
confidence: 99%